Coffee with Death - Letícia Stéfane Carneiro Gomes; Ileno Izídio da Costa (Psicopatologia Fenomenológica Contemporânea)
Previously considered a rare childhood disorder, autism today is a frequent diagnosis with increasing demand in all age groups, including people who were not diagnosed in childhood, but who perceive characteristics of this condition. This study, which is part of a broader research on the experience of Brazilian adults who were diagnosed with autism spectrum disorder (ASD) after 18 years, aims to explore the life stories, present and past, of this group of people. To this end, a qualitative research was carried out in which 12 participants were interviewed and the data were analyzed using the content analysis method, in its categorical aspect. Considering the objective of this work, in the analysis of the interviews, these categories emerged: social difficulty as the central point, sensory issues, language difficulties and naivety, rigidity/repetitive behavior, and facilities/advantages that autism brought. It was observed that social difficulties remained a central issue, even in a group of adults with mild autism, as well as sensory complaints, difficulty understanding figurative language and rigidity. Attentional hyperfocus is cited as something positive, that brings facilities to everyday life. It was concluded that the characteristics described above are present in the lives of this group of autistic people, with significant disadvantage to their daily lives.